Differential response of nano zinc sulphate with other conventional sources of Zn in mitigating salinity stress in rice grown on saline-sodic soil. (June 2023) - Ahmed, Rubaz; Zia-ur-Rehman, Muhammad; Sabir, Muhammad; Usman, Muhammad; Rizwan, Muhammad; Ahmad, Zahoor; Alharby, Hesham F.; Al-Zahrani, Hassan S.; Alsamadany, Hameed; Aldhebiani, Amal Y.; Alzahrani, Yahya M.; Bamagoos, Atif A.
Abstract: Salinization causes the degradation of the soil and threatening the global food security but the application of essential micronutrients like zinc (Zn), improve the plant growth by stabilizing the plant cell and root development. Keeping in view the above-mentioned scenario, an experiment was conducted to compare the efficiency of conventional Zn fertilizers like zinc sulphate (ZnSO4 ), zinc ethylene diamine tetra acetic acid (Zn-EDTA) and advance nano Zn fertilizers such as zinc sulphate nanoparticles (ZnSO4 NPs), and zinc oxide nanoparticles (ZnONPs) (applied at the rate of 5 and 10 mg/kg) in saline-sodic soil. Results revealed that the maximum plant height (67%), spike length (72%), root length (162%), number of tillers (71%), paddy weight (100%), shoot dry weight (158%), and root dry weight (119%) was found in ZnSO4 NPs applied at the rate of 10 mg/kg (ZnSO4 NPs-10) as compared to salt-affected control (SAC). Similarly, the plants physiological attributes like chlorophyll contents (91%), photosynthesis rate (113%), transpiration rate (106%), stomatal conductance (56%) and internal CO2 (11%) were increased by the application of ZnSO4 NPs-10, as compared to SAC. The maximum Zn concentration in root (153%), shoot (205%) and paddy (167%) found in ZnSO4 NPs-10, as compared to control. In the body of rice plants, other nutrients like phosphorus and potassium were also increased by the application of ZnSO4 NPs-10 and soil chemical attributes such as sodium and sodium adsorption ratio were decreased. The current experiment concluded that the application of ZnSO4 NPs at the rate of 10 mg/kg in salt-affected paddy soil increased the growth, physiology, up take of essential nutrients and yield of rice by balancing the cationic ratio under salt stress. Graphical abstract: Image 1 Highlights: Different zinc sources were used for salt tolerance in rice crop. ZnSO4 nanoparticles were most effective in increasing salt-stressed plant growth. ZnSO4 NPs increased Zn, P, K contents in tissues than other Zn sources. ZnSO4 NPs increased AB-DTPA extractable Zn in soil than other Zn sources.